Pengembangan Usaha UMKM Catering Di Desa Dongos Untuk Meningkatkan Perekonomian Rumah Tangga - Afiq, Choirul; Nafi’ah, Annihayatun; Shofiyanah, Faisyatus; Sofiana, Nina (Universitas Islam Nahdlatul Ulama Jepara, 2023)
A good economy will have a positive impact on various aspects, such as health, education and the economy. The existence of UMKM in Dongos Village provides a great opportunity for employment for the community, and can be used as one of the Local Original Income Sources. The methods used in carrying out this activity are data collection techniques, training, product development and business licensing assistance. Community service activities in collaboration with